2012
DOI: 10.1093/arclin/acs098
|View full text |Cite
|
Sign up to set email alerts
|

Executive Dysfunction Is the Primary Cognitive Impairment in Progressive Supranuclear Palsy

Abstract: Cognitive difficulties appear to be a more prevalent clinical feature in progressive supranuclear palsy (PSP) than previously thought, and significant cognitive impairment is prevalent in a majority of patients PSP patients not considered clinically demented. The neurocognitive performance of 200 patients with PSP across multiple sites was examined with a variety of commonly used neuropsychological tests. Results indicate primary executive dysfunction (e.g., 74% impaired on the Frontal Assessment Battery, 55% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
45
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(51 citation statements)
references
References 34 publications
5
45
1
Order By: Relevance
“…Finally, the third cluster in PSP covered a region of left Crus I/II and lobule VIIb that has been implicated in the ECN, which fits with executive dysfunction being the most common cognitive symptom in the disease 62. Based on these findings, the cerebellum may be involved in motor symptoms of PSP and in cognitive-affective changes.…”
Section: Discussionmentioning
confidence: 63%
“…Finally, the third cluster in PSP covered a region of left Crus I/II and lobule VIIb that has been implicated in the ECN, which fits with executive dysfunction being the most common cognitive symptom in the disease 62. Based on these findings, the cerebellum may be involved in motor symptoms of PSP and in cognitive-affective changes.…”
Section: Discussionmentioning
confidence: 63%
“…Paviour et al [7] showed also that lexical fluency and motor series subscores from FAB correctly classified 70% of the PSP, MSA and PD patients. In Gerstenecker et al's study [4] lexical fluency mean scores were also the lowest subscores obtained by patients with PSP. Language contribution to FAB score and its discriminant validity seems prominent.…”
Section: Discussionmentioning
confidence: 81%
“…Neuropsychological profile of PSP is supposed to be dominated by executive dysfunction: difficulties with initiation, planning multi-stage activities, impulsivity and perseveration [4]. However, a subset of PSP patients develop speech and language deficits that may be as severe as corresponding to non-fluent progressive aphasia and/or progressive apraxia of speech (PSP-PNFA), which is in line with PSP as a part of Pick Complex spectrum [3], but may also be only an additional feature.…”
Section: Introductionmentioning
confidence: 99%
“…Executive function is often the only reported neuropsychological deficit in the typical PSP (Richardson's) syndrome, [17-19] and individuals with worse color trails scores, a measure of executive function, declined at a faster rate. Surprisingly, the broader RBANS neuropsychological battery which includes tests of memory, attention, language and visuospatial function was also sensitive to change over one year, and individuals with more global cognitive impairments on RBANS at baseline had higher rates of annual PSPRS change.…”
Section: Discussionmentioning
confidence: 99%